Lazy Evaluation: From natural semantics to a machine-checked compiler transformation - Breitner, Joachim (KIT Scientific Publishing, 2016)
In order to solve a long-standing problem with list fusion, a new compiler transformation, "Call Arity" is developed and implemented in the Haskell compiler GHC. It is formally proven to not degrade program performance; the proof is machine-checked using the interactive theorem prover Isabelle. To that end, a formalization of Launchbury's Natural Semantics for Lazy Evaluation is modelled in Isabelle, including a correctness and adequacy proof.